IMPACT OF PULMONARY REHABILITATION ON SELF-CARE HYGIENE, DRESSING/UNDRESSING AND WALKING IN PATIENTS WITH CHRONIC RESPIRATORY DISEASE - Luis Gaspar; Paula Martins (Associação Portuguesa dos Enfermeiros de Reabilitação, 2018)
Patients with chronic respiratory disease (CRD) have impaired respiratory process, with a high impact on self-care, namely caused by dyspnoea and fatigue due to immobility induced by the disease. The relevance of this study is to know the impact of pulmonary rehabilitation programs (PRP) on self-care hygiene, dressing / undressing and walking. This is a quasi-experimental study that included CRD patients admitted to PRP and the impact of CRD on self-care was assessed at the beginning and at the end of the PRP. Thirty eight patients were included in the study (71.9% men), median ages 67 years (± 15.6) and FEV1% median of 39.51%. Statistical improvements (p < 0.001) and clinically significant were found in all self-care studied. The data from this study allow us to conclude that this PRP improves functional independence for the Hygiene, Dressing / Undressing and Walking self-care evaluated by the London Chest Activity Scale of Daily Living in CRD patients.